Tinjauan Hukum Islam terhadap Denda Penjadwalan Ulang Pembiayaan Mikro Murabahah di Bank Syariah Mandiri Cabang Dumai Provinsi Riau - Maulidizen, Ahmad (LP2M IAIN kUDUS, 2018)
Many Syariah banks in Indonesia are experiencing problematic financing because customers can not pay their debt installments, then the bank takes the settlement step by rescheduling the debt installment. In the process the bank charges a fee to the customer and this incriminates the customer. This research was conducted to analyze Islamic law against the cost charged to the customers in the process of rescheduling micro murabahah financing conducted by Bank Syariah Mandiri Branch Dumai Riau Province. This research uses data collection method with observation method, interview and library data, then analyzed by using inductive, deductive and comparative method. The results of this study conclude that the cost of micro-financing rescheduling in Bank Syariah Mandiri Branch Dumai Riau Province is not fully in accordance with Fatwa of Shariah and National Shari'ah Council Fatwa that has not been implemented, ie the bank charges the customer in rescheduling in addition to the actual cost required for the rescheduling process. And the authors provide suggestions for improving this by (1) providing the time period so that the customer can afford to pay, (2) the conversion of the financing contract of the murabahah to qard financing, and (3) rescheduling by charging real costs at no cost others.